STUDY OF CHARACTERISTICS ACTIVITIES JATINANGOR HIGH EDUCATION MULTIPLIER AGAINST LOCAL ECONOMY - DENNY SURBAKTI (NIM 25407059), ASEP
Determination Jatinangor as the area of higher education cause the population to draw from outside Jatinangor to perform activities of higher education in the area of higher education as a civitas academic. The large number of civitas academic activities that make higher education must be supported with activities and supporting facilities that serve the needs of civitas academic, and this is an opportunity for the local economy. However, if the economic opportunities can not be used (provided) by local residents, the newcomers will take the economic opportunities are. As a result of the local Jatinangor no benefit whatsoever, and only as a spectator only temporary migrants enjoy the benefits. Based on this study will then assess the impact of higher education to the local economy Jatinangor. Method used in this research is a method of description. The method will give you a description of the characteristics of the activities supporting higher education and job opportunities for residents Jatinangor because of the higher education activities for both locals and migrants. Based on the results of the research revealed that the activities of higher education in Jatinangor impact on local economic activities generate Jatinangor with the support of higher education that provides civitas academic needs and the job opportunities for local residents Jatinangor, either as owner or as supporting the activities of labor activity in support of higher education . However, the role of the local population is very limited compared to the newcomer. This is marked with a number of local residents supporting the activities of relatively small due to lack of capital compared with immigrants who have capital and scale that is greater. To enhance the role of the local activities in the provision of support, either as owners or employees of supporting education or improve the welfare of the local existence of the necessary institutions that can provide the capital with just mild interest in building a business and provide adequate training business. And need to be made a regulation that restrict land sales to residents outside Jatinangor permits and limit the activities supporting the development of education with priority for local residents.